Information and Communication Technology (ICT) Based Teaching-learning Activities on Medical Program in COVID-19 with Prospects and Privileges - Yusuf, Riti; Iqbal, Jalaluddin Md; Hasan, Md Ifta Khiarul; Moon, Kawsar Jahan; Nahar, Sharmin (Sir Salimullah Medical College Journal, 2023)
Information and Communication Technology (ICT) is enabling a concrete learning activity along with proved academic achievement. It is one of the most dynamic techniques, which can help to utilize the aptitude of recent science. E-learning and M-learning can further provide easy access to education for many and providing good teachers closer to students too. This article is an initial trial to review prior studies on ICT based teaching-learning activities for technological advancement in medical sector. The sector has improved in using ICT in their professional routines. A high-quality education can run only when it is supported by the institutions within the framework with a coherence to national and regional policies. Very few trials and setup has been built to run this. But further transformation is necessary to provide easy access towards them. This study adopted a narrative literature review study, involving recent relevant scholarly researches of medical sector and education development program, online monthly magazine and online websites with highlights on some very important integral issues- the perspective of COVID related E-learning, recent ICT Tools, Bangladesh towards new era of ICT, the key factors to achieve E-learning and M-learning and some needful as for security purpose. This expectantly will help to explore ICT state in Bangladesh on COVID-19 and some further steps needed to fetch the medical sector forward, towards this initiative to cope up with other countries, in a planned way. This study contributes to a better understanding of the under researched topic of; ICT in teaching-learning activities, which came forward at the time of COVID-19. Sir Salimullah Med Coll J 2023; 31: 34-40